Effect of Poultry Manure and Granite Rock Dust Applications on the Chemical Properties of Soil under Amaranthus cruentus at Organic Farm in Abeokuta, Ogun State, Nigeria - S. D. Oyekunle; O. O. Akinbile; G. O. Elumalero; U. E. Brownson; T. I. Akinremi; A. M. Samuel; G. C. Gbaruko (Journal of Applied Sciences and Environmental Management)
The objective of this paper was to evaluate the effect of poultry manure and the time of application of granite rock dust on the chemical properties of soil under Amaranthus cruentus at an organic farm in Abeokuta, Ogun State, Nigeria, using standard procedures. Results of physical and chemical properties of soil show that pH = [7.18], organic carbon= [1.84], nitrogen = [0.09], phosphorus = [5.18 mg/kg], potassium = [1.29 cmol/kg], calcium = [2.69 cmol/kg], magnesium = [0.96 cmol/kg], manganese = [5.48 mg/kg], zinc = [1.48 mg/kg], and copper = [0.29 cmol/kg].  Application of poultry manure and rock dust affected these values as pH (8.46, 6.97); % OM (22.33, 82.56), % TN (3.42, 9.88), % OC (31.01, 7.56), % Total P (1.87, 4.28), % Ca (2.89, 0.76), % Mg (0.46, 1.89), % K (2.89, 0.78), % Na (0.99, 12.04), % S (0.38, 0.08), Cu (mg/kg) [362, 3.14], Fe (mg/kg) [1982, 2.89], Zn (mg/kg) [283.5, 0.17], Mn (mg/kg) [281, 1.88]. This study concludes that Amaranthus cruentus could be grown by applying some poultry manure and rock dust to improve the soil chemical.